2017
DOI: 10.1002/hbm.23920
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity alterations in post‐traumatic stress disorder

Abstract: Post-traumatic stress disorder (PTSD) is a debilitating condition which can develop after exposure to traumatic stressors. Seventy-five adults were recruited from the community, 25 diagnosed with PTSD along with 25 healthy and 25 trauma-exposed age- and gender-matched controls. Participants underwent clinical assessment and magnetic resonance imaging. A previous voxel based morphometry (VBM) study using the same subject cohort identified decreased grey matter (GM) volumes within frontal/subcortical brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 88 publications
6
39
0
Order By: Relevance
“…Mueller-Pfeiffer et al (2013) also reported a diminished neural activity in the visual system in PTSD patients. Likewise, studies have reported white matter abnormalities, suggesting alterations in neural pathways (Akiki, Averill, & Abdallah, 2017;O'Doherty et al, 2018). An alternative explanation for the EPN inhibition might be an adaptive adjustment of emotion processing to arousing material after experiencing traumatic stress with a subsequent heightened arousal state.…”
Section: Discussionmentioning
confidence: 99%
“…Mueller-Pfeiffer et al (2013) also reported a diminished neural activity in the visual system in PTSD patients. Likewise, studies have reported white matter abnormalities, suggesting alterations in neural pathways (Akiki, Averill, & Abdallah, 2017;O'Doherty et al, 2018). An alternative explanation for the EPN inhibition might be an adaptive adjustment of emotion processing to arousing material after experiencing traumatic stress with a subsequent heightened arousal state.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report microstructural evidence that structural connectivity between the left and right hippocampus may also be disrupted in PTSD. While many studies have reported that PTSD is associated with alterations in the cingulum bundle [9][10][11][12][13]16,18,21,[23][24][25][26][27][28][29]31,32,36 , which has a hippocampal component, the tapetum has not yet emerged for several possible reasons. Many prior studies took an ROI approach, which limited analyses to pre-determined regions that frequently omitted the tapetum, a small region often grouped with other tracts such as the splenium or posterior thalamic radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of white matter microstructure in PTSD have reported inconsistent results. The majority report that PTSD is associated with lower FA [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , but some report higher FA [25][26][27][28][29][30][31] , higher and lower FA in different regions 32 , or null results [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations